FROM DECADENCE TO TEURGY (CONNECTIONS IN GENESIS OF CZECH AND RUSSIAN LITERATURE AT THE END OF 19TH AND BEGINNING OF 20TH CENTURY) (Филологический класс, 2019)
The article focuses on comparative analysis of aesthetic philosophical concepts of Czech and Russian symbolism at the end of 19th and the beginning of 20th century. The attention is predominantly paid to interpretation of selected theoretical studies and essayistic work by Czech and Russian followers of decadent-symbolist and symbolist aesthetics. In this article we are showing inner connections in genesis of aesthetic-philosophical system, which, in context of East and West-Slavonic literatures, represents gradual heading from decadent-symbolic aesthetics to broader trans-cultural syntheses. Above all, we follow gradual and fluent evolution from the concept of autonomous model of beauty to the principal of theurgy, which understands art as a cosmogonic power. In the first decadent-symbolist phase, Czech and Russian literature were carried by overcoming the reality by refusing of materialistic existence and by the way to spiritual visions and dreaming. The world of art had become a defence of clear aesthetic values, transcendent desire and metaphysical dream with sense of secret of human life, found in extra-sensual sphere of spiritual world of human. In aesthetic theories of both, Czech and Russian followers of decadent-symbolist aesthetics, we can find gradual tendencies to overcome decadent approaches to the integral understanding of the work of art as a high phase of symbolism. However, that was fully defined later by next art generation who started understanding art creating in its broader meaning as theurgy, using the words of the Russian philosopher V. Solovjov. Work of art and essayistic work of followers of this this phase of symbolism is represented by the idea of theurgy, idea of art which possesses mystic power, the idea of “all-human” art together with cognitive act. Art is seen mostly as a complex way of thinking and understanding of the world and the way of existence there. As the most important thing it was operated with finding of new perceptive ways and expressing and reaching the state of existence when the artistic images would not only evoke the impression of beauty but, at the same time they would work as the means of cognition.